HIV treatment is associated with a twofold higher probability of raised triglycerides: pooled analyses in 21 023 individuals in sub-Saharan Africa. (8th May 2018) - Ekoru, K.; Young, E. H.; Dillon, D. G.; Gurdasani, D.; Stehouwer, N.; Faurholt-Jepsen, D.; Levitt, N. S.; Crowther, N. J.; Nyirenda, M.; Njelekela, M. A.; Ramaiya, K.; Nyan, O.; et al.
Abstract : Background: Anti-retroviral therapy (ART) regimes for HIV are associated with raised levels of circulating triglycerides (TGs) in western populations. However, there are limited data on the impact of ART on cardiometabolic risk in sub-Saharan African (SSA) populations. Methods: Pooled analyses of 14 studies comprising 21 023 individuals, on whom relevant cardiometabolic risk factors (including TG), HIV and ART status were assessed between 2003 and 2014, in SSA. The association between ART and raised TG (>2.3 mmol/L) was analysed using regression models. Findings: Among 10 615 individuals, ART was associated with a two-fold higher probability of raised TG (RR 2.05, 95% CI 1.51–2.77, I2 = 45.2%). The associations between ART and raised blood pressure, glucose, HbA1c, and other lipids were inconsistent across studies. Interpretation: Evidence from this study confirms the association of ART with raised TG in SSA populations. Given the possible causal effect of raised TG on cardiovascular disease (CVD), the evidence highlights the need for prospective studies to clarify the impact of long term ART on CVD outcomes in SSA.